2019
DOI: 10.3390/s19214728
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic Signatures Exhibited by Plasmonic Effects in Au Nanoparticles with Cells

Abstract: The evolution of the optical absorptive effects exhibited by plasmonic nanoparticles was systematically analyzed by electronic signals modulated by a Rössler attractor system. A sol-gel approach was employed for the preparation of the studied Au nanoparticles embedded in a TiO2 thin solid film. The inclusion of the nanoparticles in an inhomogeneous biological sample integrated by human cells deposited in an ITO glass substrate was evaluated with a high level of sensitivity using an opto-electronic chaotic circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Nevertheless, all the participants enrolled in the study were healthy, assuming a stable water balance. Fourth, previous evidence has highlighted the importance of additional conditions of the measurements for different ages, i.e., the activity of the cells gives rise to a different dependence on electrical frequency [32]. Specifically, a study by Martines-Arano et al [32] has shown that electrical sensing of the cell may have different aging absorption and by using bioelectrical impedance, additional cell malfunctions can be observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, all the participants enrolled in the study were healthy, assuming a stable water balance. Fourth, previous evidence has highlighted the importance of additional conditions of the measurements for different ages, i.e., the activity of the cells gives rise to a different dependence on electrical frequency [32]. Specifically, a study by Martines-Arano et al [32] has shown that electrical sensing of the cell may have different aging absorption and by using bioelectrical impedance, additional cell malfunctions can be observed.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, previous evidence has highlighted the importance of additional conditions of the measurements for different ages, i.e., the activity of the cells gives rise to a different dependence on electrical frequency [32]. Specifically, a study by Martines-Arano et al [32] has shown that electrical sensing of the cell may have different aging absorption and by using bioelectrical impedance, additional cell malfunctions can be observed. Finally, we did not assess outside nor skin temperature, which change resistance measurements of the bioelectrical impedance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the evolution of the optical absorptive effects exhibited by plasmonic nanoparticles enable the improvement in the biological sensing. One of the approaches is by using a chaotic signal circuit, which can exhibit powerful nonlinear optical responses arising from chaotic behavior in the areas of photonics and plasmonics [ 129 ]. By using this approach, the small changes in plasmonic signals of the nanoparticles can be recorded with the assistance of near-resonance optical excitations.…”
Section: Discussionmentioning
confidence: 99%
“…The enhancement factor (EF) directly depends on the structure and plasmonic hot spots of SERS substrates, which makes their rational design and reproducible fabrication a key challenge in advancing SERS applications, which is also applicable for live cell imaging [7]. Research on SERS is ongoing [8] and colloidal NPs render several advantages, such as highly reproducible and cost-effective synthesis via bottom-up strategies and tailoring their optical properties via tuning particle shape and size, aggregation, surface functionalization, and the application of external stimuli (e.g., visible light irradiation [9]).…”
Section: Introductionmentioning
confidence: 99%